Narrativa e representação nos quadrinhos: a restauração Meiji (1868) nos mangás - Feijó, Luiz Carlos Coelho (2013)
Relatively recent in Brazil, the manga won fans of all ages and genres through titles like Dragon Ball and Dragon Ball Z, Rurouni Kenshin, One Piece and others. Many of its stories have historical background or reference parts of Japanese history, especially of samurai and shinobi (ninja), which has awakened the interest of Brazilian readers, hitherto accustomed to Western stories that mostly were purely fictional. All this notoriety gained by manga in the West drew the attention of Western scholars, among which we mention Sonia Bibe Luyten (2000); Paul Gravett (2006) and Robin Brenner (2007), leading them to conduct research ranging from appearance manga of the role played by them in Japanese culture today. Taking this into consideration, this study aimed at evaluating how three mangaká (Chrono Nanae, Watsuki Nobuhiro and Sorachi Hideaki) make use of their works to convey to his readers his view on certain events in the Meiji Restoration, whether through narrative or the representation of historical characters inserted into his plots